ChemInform Abstract: Silica‐Supported Boric Acid Catalyzed Synthesis of Dihydropyrimidin‐2‐ones, Bis(indolyl)methanes, Esters and Amides. Issue 20 (20th May 2014) - Kumar, Vishal; Singh, Chitra; Sharma, Upendra; Verma, Praveen K.; Singh, Bikram; Kumar, Neeraj
Abstract Silica‐supported boric acid is found to be a green, efficient, and reusable catalyst for the synthesis of the title compounds under solvent‐free conditions.